Teaching and learning activities to educate nursing students for interprofessional collaboration: A scoping review. - Murdoch, Natalie L.; Epp, Sheila; Vinek, Jeanette (Journal of Interprofessional Care, 2017)
To prepare new graduates with the knowledge, skills, and attitudes to engage in effective interprofessional collaboration (IPC) in practice, healthcare professional programmes need to ensure their curriculum provides opportunities for interprofessional education (IPE) and IPC. To strengthen IPE within an undergraduate curriculum and meet the professional requirements set out by regulatory bodies to prepare new graduate nurses to achieve IPC competencies, a curriculum initiative was developed to expand IPE across the four years of the Baccalaureate of Science in Nursing (BSN) programme. The purpose of this scoping review was to identify published teaching-learning activities in undergraduate nursing programmes to inform the development and integration of IPE curricula. The literature included was identified by searching the following electronic databases: EMBASE and EBSCO (CINAHL, Medline, Education Research Complete, ERIC). The search was limited to articles with abstracts published between 2008 and 2016 in the English language. All ten studies that met inclusion criteria reported students’ perceived interprofessional education as valuable in facilitating their achievement of IPC competencies. Interprofessional education is an approach for preparing nursing students with knowledge, skills, and attitudes to achieve IPC competencies and therefore, urgently needs to become more prevalent in nursing curricula. Educators can use a variety of IPE teaching-learning activities to support students’ achievement of IPC competencies in order to prepare new practitioners to engage in effective IPC in a variety of healthcare milieus. Nurse educators are encouraged to intentionally integrate learning opportunities into current and future undergraduate nursing education to prepare collaborative ready graduate nurses.